Draft Annual Plan 1993-94 Government of Rajasthan - Planning Commission (Planning Commission, 1992)
Rajasthan State, in its present form, is a conglomeration of 19 princely States and 3 chiefships which varied in size, population, administrative efficiency and socioeconomic development. Administratively, Rajasthan is divided into 30 districts, which are further sub-divided into 213 tehsils and 237 development blocks. The area of 3.42 lakh sq. km. of Rajasthan makes it the second largest State in the country. The population of the State, according to 1991 censuses 4.39 crores. It has a long international frontier with Pakistan and is adjacent to the State of Punjab, Haryana, Uttar Pradesh, Madhya Pradesh and Gujarat.
Planning Department